A Study of Bicomplex Gamma and Riemann Zeta Functions and their Conjugations. Issue 1 (1st May 2022) - Kashyap, Muskan; Singh, Sukhdev
Abstract: In this paper, we have studied the bicomplex gamma and Riemann zeta functions. The relation between bicomplex gamma function and bicomplex Riemann zeta function has been established. Their properties under different conjugations and moduli in the bicomplex space are also studied in details.